Culture “NIRMENIRAN” (Herbal Medicine) on Improving The Nutritional Status Of Toddlers - Wardita, Yulia; Salat, Sri Yunita Suraida; Huzaimah, Naili; Adrian, Maulana Widi; Anisa (Journal of Applied Nursing and Health, 2024)
Background: The region is known for its high prevalence of malnutrition cases, making it a significant concern for public health. The local health center has noted instances of malnutrition in certain areas, prompting efforts to investigate potential contributing factors and solutions. This study aims to explore the relationship between the culture of consuming local food, "Nirmeniran," and its potential impact on improving the nutritional status of toddlers in the community. Methods: Quantitative with correlation or association research type. The respondents of this study were mothers of toddlers in Longos Village. The sampling technique used the Random Sampling technique, with a sample of 63 mothers of toddlers. Data collection used questionnaires and BB/TB observations. Statistical tests used Spearman's Rho Correlation test. Results: Part Big mother toddlers in Village Longos often give drinks or herbal medicine containing local food, “Nirmeniran,” to their children, and most toddlers have good nutritional status. The results of statistical tests show ρ value = 0,000 with mark α = 0.05, So ρ (0,000) < α (0.05), which means There is a connection between culture consumption food local “Nirmeniran” towards improving the nutritional status of toddlers in Longos Village. Conclusion: The cultural consumption of "Nirmeniran" is linked to improved nutritional status in toddlers. Most mothers in the area frequently provide drinks or herbal medicine containing this local ingredient, showing its potential benefits.